(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Marketing is a place where the buying and selling of goods and services. The sandy’s (santhalu) full fill the daily stock requirements of the local people. The present paper will find out to the various problems faced by the sandy’s sellers. Generally, the sandy’s are conduct open mass area or street roads. In this sandy very helpful for house holders for purchase the verity of goods and services. In this sandy’s Specially for vegetable and other home requirement items are available. The present study finds out to the various problems faced by sandy’s in selected areas of Visakhapatnam city.